2003
DOI: 10.1039/b309851f
|View full text |Cite
|
Sign up to set email alerts
|

HONO decomposition on borosilicate glass surfaces: implications for environmental chamber studies and field experiments

Abstract: Nitrous acid (HONO) is the major source of OH in polluted urban atmospheres, so an understanding of its formation and loss processes both in urban atmospheres and in laboratory systems is important. Earlier studies over a limited range of conditions showed that HONO is taken up and undergoes reaction on surfaces. We report here a comprehensive set of studies of the decay of HONO and the formation of gas phase products over a range of initial HONO concentrations (0.1-11 ppm) at 1 atm pressure in N 2 at 296 K an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 71 publications
8
77
0
Order By: Relevance
“…It should be pointed out that the kinetic data were measured in the dark in this work, and other factors such as adsorbed HNO 3 have not been considered. It is necessary to investigate in the future whether irradiation has an enhancement effect on these reactions like that on Saharan sand 23 and whether the co-absorbed species, such as HNO 3 , which were found to promote HONO decomposition on borosilicate glass surfaces, 49 have an influence on the HONO yield.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…It should be pointed out that the kinetic data were measured in the dark in this work, and other factors such as adsorbed HNO 3 have not been considered. It is necessary to investigate in the future whether irradiation has an enhancement effect on these reactions like that on Saharan sand 23 and whether the co-absorbed species, such as HNO 3 , which were found to promote HONO decomposition on borosilicate glass surfaces, 49 have an influence on the HONO yield.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…This ion pair reacts with surface film water to form adsorbed HONO and HNO 3 . The HNO 3 remains on the surface while HONO is either displaced into the gas phase by the competitive adsorption between water and HONO, 30 or undergoes secondary chemistry to produce gaseous NO, NO 2 , and small amounts of N 2 O. In order for HONO production to be first order in NO 2 , as many previous studies reported, 12,[17][18][19][20][21][22][23][24][25][26] a back reaction involving NO 2 reacting with ONONO 2 must be faster than the competing reaction with water.…”
Section: Introductionmentioning
confidence: 96%
“…The surface reactions were parameterized as gas phase processes. Because the specific details of the NO 2 heterogeneous hydrolysis mechanism are uncertain, this portion of the model is simplified to have the least number of unknown variables and yet still capture the essence of what is known about the heterogeneous hydrolysis of NO 2 : the reaction is first order in NO 2 and water vapor, 12,[17][18][19][20][21][22][23][24][25][26] there is a competitive adsorption on the surface between H 2 O and HONO, 30 and HONO undergoes heterogeneous reactions on the cell walls to generate NO and NO 2 .…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The present studies also show that the photochemically driven transfer of a hydrogen atom from HNO 3 Furthermore, water has been shown to displace HONO from surfaces into the gas phase in both laboratory and field studies. 107,108 Whether this is a simple competitive adsorption/ desorption process or a chemical reaction with a HONO precursor is not known. However, if a complex such as (HNO 3 )Á(N 2 O 4 ) is a precursor to HONO, the latter may be initially bound to HNO 3 when it is formed on the surface.…”
mentioning
confidence: 99%